PENGARUH PENGANGGURAN DAN JUMLAH PENDUDUK TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI NUSA TENGGARA TIMUR - Ndawareha, Yonaldin; Renggo, Yuniarti Reny; Kabubu Hudang, Adrianus (Ekonomi Pembangunan Fakultas Ekonomi, 2024)
Economic growth is an important indicator in improving people's welfare, but several factors such as unemployment and population size can affect the economic growth process. This study aims to determine the effect of unemployment and population size on economic growth in East Nusa Tenggara Province. The analysis method used is multiple linear regression analysis. The results of the study show that simultaneously, the variables of population size and unemployment have a significant effect on economic growth. Partially, the population size variable has a negative and significant effect on economic growth. While the unemployment variable has a positive and significant effect on economic growth during the period 2018-2022.